Dashboard Impact Evaluation for Primary Care and Community Health Programs - James E. Rohrer PhD, MS, BS (SAGE Publishing, 2010)
Dashboard impact evaluations are studies that assess the short-term effects of health programs on performance indicators that are of interest to senior managers. Evaluations of this type can be performed rapidly and at relatively low cost if evaluators are experienced and independent, and use standard methods. Assessment of short-term impacts can provide valuable encouragement or raise concerns that call for close monitoring or redirection of program activities. Preliminary results can be in hand as early as 60 days after a program begins operations.